Teatro social dos afetos - Fernandes, Kelly Cristina (2019)
The present research draws what we call Social Theater of the Affect (STA), a methodology based on the Theater of the Oppressed, which considers affect as a central political concept and reflects on the complexity and nuances of the relationship between the oppressed and the oppressor. The research uses secondary data, provided by the reports of a project in Theater of the Oppressed which consisted in teacher-training at an Elementary and Middle School and the creation of theater groups. The objective of these groups was to promote students’ council groups and also to challenge violence within the school. In this research, the ideas of affect, passion and power of Espinosa and Vygotsky’s idea of catharsis take center stage within the theoretical reflections and provided the structure underpinning the STA. The reports present the debates on the daily traumatic and violent conflicts, documenting how these processes of transformation are mediated by art. Among them, reports on gender issues, in particular, child sexual abuse, homophobia and chauvinism in schools and in the families were selected, as they were the most recurrent and the main typified issues that guided the idea and form of the STA. Thus, the research defends affect as a political and pedagogical issue, and also incorporating within this theory a definition of a methodology to support the collective confrontation of violence in schools. The recognition and trust that supports the commonalities between people and how this increases people’s life potential, stood out as fundamental points for this methodology. Finally, it is emphasized that the further objective of the thesis is to be a supportive resource for those who use or intend to use this methodology in groups